Food security and economic growth - Abdul Manap, Nur Marina; Ismail, Normaz Wana (Global Academic Excellence, 2019)
The world has seen continued famine, starvation and malnutrition. Starvation and malnutrition have a negative impact on health, leading to poor productivity, and thus gradually affecting overall economic growth. This paper estimates the impact of food security on the economic growth of dry-land developing countries. The objective of this study is to measures the impact of food security on economic growth directly and through poverty, life expectancy, and total employment. This study employs a dynamic panel data model known as the Generalized Method of Moments (GMM). The finding of this study has proved that food security has an impact on economic growth, especially in dry-land developing countries. This research has identified that food security has a significant positive impact on food security, as an increase in food security increases economic growth. Nonetheless, food security also has an impact on economic growth in terms of life expectancy, total employment, and poverty, whereas life expectancy and total employment with better food security have a positive impact on economic growth, reduce in poverty, achieving food security and enhancing economic growth.